PEMBUATAN PUPUK FOSFAT DARI BATUAN FOSFAT ALAM SECARA ACIDULASI - Faleh Setia Budi; Aprilina Purbasari (Diponegoro University, 2009)
Phosphate rock containing P2O5 can be used as raw material of phosphate fertilizer. Phosphate rock canbe found in many areas in Indonesia, but its P2O5-content is relative low. In this research, phosphate rockfrom Rembang (P2O5-content 11.37%) is used as raw material for phosphate fertilizer production byacidulation process using phosphoric acid solution. Operation variables are phosphoric acid concentration(10, 20, 30, 40 %-vol), spraying model of phosphoric acid solution (one hole and many holes), andspraying position of phosphoric acid solution (end, centre, end & centre). The result shows that theincrease of phosphoric acid concentration is proportional to P2O5-content in phosphate fertilizer withhighest P2O5-content in the amount of 18.29%. One-hole spraying model and end-position spraying giveshighest phosphate fertilizer yield in amount of 169.5 grams.